Origin and ontogeny of the xylopodium in Cerrado legumes: role of the hypocotyl and ecological significance - Cozin, Bruno Bonadio [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The xylopodium is commonly found in the Cerrado, but its development stages and anatomical features are not fully explained. Describing the origin of bud-bearing organs, such as the xylopodium, is important for understanding their development and relevance for post-fire resprouting in disturbed environments. Hence, our aim was to investigate the formation of the xylopodium from six Cerrado legume related to the hypocotyl region, in order to confirm the presence of such organs, as well as histochemical features and ecological implications from seedlings to adult plants in this frequently-burned ecosystem. Seeds of the six study species were collected in central-western region of Brazil, set to germinate and cultivated until the stages of four, six, nine, and twelve months. At each stage, the hypocotyl region was delimited and anatomical and histochemical analyses were performed. Through time, the hypocotyl region underwent a tuberization process, during which the cortex was progressively replaced by the formation of secondary xylem. Before the twelve-month-old stage, all species presented buds, mainly cotyledonary, and reacted to starch, phenols and pectins. The early tuberization of the hypocotyl region, the presence of buds and the accumulation of reserves show that the xylopodium formation is a fundamental process driving species persistence after fire.

O xilopódio é comumente encontrado no Cerrado, mas seus estágios de desenvolvimento e características anatômicas não são totalmente explicados. Descrever a origem dos órgãos subterrâneos especializados, como o xilopódio, é importante para compreender o seu desenvolvimento e relevância para o rebrotamento no pós-fogo em ambientes perturbados. Assim, nosso objetivo foi investigar a formação do xilopódio de seis leguminosas do Cerrado relacionadas à região do hipocótilo, a fim de confirmar a presença de tais órgãos, bem como características histoquímicas e implicações ecológicas desde plântulas até plantas adultas em ecossistemas frequentemente queimados. Sementes das seis espécies estudadas foram coletadas na região centro-oeste do Brasil, germinadas e cultivadas até as fases de quatro, seis, nove e doze meses. Em cada etapa foi delimitada a região do hipocótilo e realizadas análises anatômicas de rotina e histoquímicas. Os resultados mostraram que, com o passar do tempo, a região do hipocótilo passou por um processo de tuberização, durante o qual o córtex foi progressivamente substituído pela formação do xilema secundário. Antes da fase de doze meses de idade, todas as espécies apresentaram gemas, principalmente cotiledonares, e os testes histoquímicos revelaram presença de amido, fenóis e pectinas em sua estrutura. A tuberização precoce da região do hipocótilo, a presença de gemas e o acúmulo de reservas mostram que a formação do xilopódio é um processo fundamental que impulsiona a persistência das espécies após o fogo.
Origem e ontogenia do xilopódio em leguminosas do Cerrado: o papel do hipocótilo e implicações ecológicas
Keywords: Anatomy; Reserve compounds; Fabaceae; Buds; Belowground organs; Anatomia; Compostos de reserva; Fabaceae; Gemas; Órgãos subterrâneos